The Development of Gender Based-Teaching Material: Press and Journalistic Skills - Tahrun, Tahrun; Nasir, Muhamad; Houtman, Houtman (Jurnal Dosen Universitas PGRI Palembang, 2017)
This article presents conceptual design of gender based-teaching material for teaching âPress and Journalistic Skillâ to the students of Language and literature education department. This conceptual design is the result of the first year research finding of the two years scheduled. The teaching material developed was in the form of textbook. This teaching material was designed to improve studentsâ skill in press and journalism. To develop this instructional material, the writers used Research and Development method. The result of the research showed that the content of the textbook of press and journalism covers d the scope of communication, the nature, process and components of communication, mass communication and press/jurnalism, jurnalist, mass media, news, the ethics of journalism, and the press law. This textbook is ended with references.Â Â Key words: teaching material, gender, press, journalistic